2020
DOI: 10.1155/2020/4196548
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Cinnamaldehyde against Mesenteric Ischemia-Reperfusion-Induced Lung and Liver Injuries in Rats

Abstract: The aim of this study was to characterize and reveal the protective effects of cinnamaldehyde (CA) against mesenteric ischemia-reperfusion- (I/R-) induced lung and liver injuries and the related mechanisms. Sprague-Dawley (SPD) rats were pretreated for three days with 10 or 40 mg/kg/d, ig of CA, and then induced with mesenteric ischemia for 1 h and reperfusion for 2 h. The results indicated that pretreatment with 10 or 40 mg/kg of CA attenuated morphological damage in both lung and liver tissues of mesenteric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Moreover, trans-cinnamaldehyde treatment uncovered anti-inflammatory actions by downregulating COX-2 expressions compared with methotrexate alone [ 102 ]. Furthermore, cinnamaldehyde treatment significantly attenuated inflammation in mesenteric liver injuries by downregulating the expression of inflammation-related COX-2 [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, trans-cinnamaldehyde treatment uncovered anti-inflammatory actions by downregulating COX-2 expressions compared with methotrexate alone [ 102 ]. Furthermore, cinnamaldehyde treatment significantly attenuated inflammation in mesenteric liver injuries by downregulating the expression of inflammation-related COX-2 [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the levels of TP, ALB, and IgG were increased in fish fed CNE [62]. TP, ALB, and IgG are indicators for assessing various immunity in the diet, and the increase in their levels is [65]. In addition to difference in species, environmental factors, as well as different metabolic cycles, could be the main reasons for differences in protein metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…otakii . On the other hand, studies showed that CNE could restore the activities of AST and ALT in damaged liver tissue and downregulate the expression of interleukin-6 (IL-6), interleukin-1 β (IL-1 β ), cyclooxygenase-2 (Cox-2), and tumor necrosis factor receptor type-2 (TNFR-2) inflammation-related protein and genes [ 65 ]. In addition to difference in species, environmental factors, as well as different metabolic cycles, could be the main reasons for differences in protein metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal I/R injury is also found to cause extensive cell apoptosis [ 16 , 52 ]. Inhibition of cell death mechanism by blocking apoptotic markers (Bax and caspase 3/9) [ 22 , 28 , 53 55 ] or overexpressing antiapoptotic markers (Bcl2) [ 22 , 28 , 54 56 ] prevents the pathogenesis of intestinal I/R injury. Therefore, compounds with multiple beneficial effects of tissue protection, anti-inflammatory, antioxidant, and antiapoptosis, especially natural active substances, are expected to play a protective role in ameliorating intestinal I/R injury.…”
Section: Discussionmentioning
confidence: 99%